A text in a text and about a text - Kleszczowa, Krystyna (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
On the basis of ample literature devoted to parenthesis in the modern Polish language, the author seeks the instruments for the recognition of instances of parenthesis in old texts, in the study of which we lack linguistic competence, and in the study of which we lack prosodical hints (these constitute a substantial property of parenthesis). After Maciej Grochowski, it assumes that parenthesis is an expression which occurs in interposition, it uses the hints which are provided by punctuation signs (even though the latter differ from the ones that are used today), it takes into account the constitutive elements of interjections (verba dicendi). A hint in the indication of parenthesis in an old text is the convergence with the constructions which are familiar to this day (e.g. że tak powiem [ut ita dicam]). One should emphasize that one hint is not sufficient in the recognition of parenthesis in a text which was written centuries ago — usually the hints cross over and supplement each other. The pursuit of parenthesis facilitated the discovery of such types which are not featured in the Polish language (with czyli, rzekę and mówię), the inference about the existence of parenthesis even when it was not registered, cf. zaiste, zawierne, after the pattern of interjections with za pewne ‘surely’. Instances of parenthesis were the sources of certain particles — epistemic (e.g. niewątpliwie, z pewnością, pewnie), generalizing (np. generalnie, ogólnie), conclusion-related (dokładnie, innymi słowy, mianowicie), as well as particles of supplementation (na dodatek, w dodatku, ponadto). Thus, the article continues the problems which are discussed in the monograph entitled U źródeł polskich partykuł. Derywacja funkcjonalna, przemiany, zaniki (Katowice 2015).